2011
DOI: 10.1017/s0267190511000122
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Communicative and Task-Based Language Teaching in the Asia-Pacific Region

Abstract: Communicative language teaching (CLT) and task-based language teaching (TBLT) have been widely adopted in the Asia-Pacific region, with a number of Asian countries strongly promoting CLT and TBLT in their curricula and English language education policies. Despite their popularity, a number of challenges have arisen in connection with implementing CLT and TBLT in Asian classrooms. The challenges that have emerged include (a) conceptual constraints (e.g., conflicts with local values and misconceptions regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
222
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(251 citation statements)
references
References 61 publications
(93 reference statements)
8
222
0
3
Order By: Relevance
“…Similarly, Butler (2011) has also identified the enormous use of first language by the learners in Asian countries. He further explained that in order to achieve a greater absorbing of 'task', the use of L1 by the students is considerably needed.…”
Section: Tblt In Asian Countries: Phenomenon and Major Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Butler (2011) has also identified the enormous use of first language by the learners in Asian countries. He further explained that in order to achieve a greater absorbing of 'task', the use of L1 by the students is considerably needed.…”
Section: Tblt In Asian Countries: Phenomenon and Major Constraintsmentioning
confidence: 99%
“…We should acknowledge that the practice of Task-Based Language Teaching (TBLT) has been flourishing around the world; numerous of research has appeared with reports on its compatibility in the scope of Asian countries (Nunan, 2006;Littlewood, 2007;Butler, 2011;Lai, 2015). In regard to this concern, nevertheless, it is identified that the study regarding TBLT in Indonesian context is limited.…”
mentioning
confidence: 99%
“…More recently school-based assessment has begun to make inroads into Asia (e.g., Butler, 2011;Chong, 2009;Davison, 2007). However, studies to date in Malaysia have primarily focused on implementation issues of SBA.…”
Section: Literature Reviewmentioning
confidence: 99%
“…He approved superiority of Task-based language teaching over traditional methods. At the same time in Asia, Butler (2011) investigated implementation of communicative and Task-based language teaching in Asia-Pacific region. The researcher found TBLT being adopted and used in many countries, while facing some challenges like: conceptual constraints, classroom-level constraints and societal institutional level constraints.…”
Section: International Journal Of Learning and Developmentmentioning
confidence: 99%